2021
DOI: 10.1111/pan.14332
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of landmark technique and ultrasound‐guided caudal epidural injection in pediatric population: A systematic review and meta‐analysis

Abstract: Caudal epidural block is a common regional anesthesia technique for lower limb and infraumbilical surgeries in children. 1 It makes up to 40% of all regional anesthesia blocks and more than 90% of single injection and 25% of continuous catheter neuraxial blocks in the pediatric age group. 2 The caudal block is highly popular in children because of multiple reasons. Firstly, the epidural space is easy to access due to non-ossification of ligaments. The spread of local anesthetic may be facilitated by fluidity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[ 26 ] Additionally, it has also been shown that ultrasound-guided epidural injections neither improve the success rate nor shorten the duration of the block; rather, they have a higher success rate of first puncture and a lower complication rate. [ 27 ] Dietrich et al[ 7 ] found that the mean effective dose of patients with TFLEI under the guidance of fluoroscopy is 0.24±0.22 mSv. The interventional physician's radiation measurements under the guidance of X-ray fluoroscopy are as follows: body, (0.42±0.99)x10 3 mSv; wrist, (1.44±2.69)x10 3 mSv.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Additionally, it has also been shown that ultrasound-guided epidural injections neither improve the success rate nor shorten the duration of the block; rather, they have a higher success rate of first puncture and a lower complication rate. [ 27 ] Dietrich et al[ 7 ] found that the mean effective dose of patients with TFLEI under the guidance of fluoroscopy is 0.24±0.22 mSv. The interventional physician's radiation measurements under the guidance of X-ray fluoroscopy are as follows: body, (0.42±0.99)x10 3 mSv; wrist, (1.44±2.69)x10 3 mSv.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review underlines this finding. So, ultrasound-guided caudal injection results in higher first puncture success and lower incidence of complications compared to landmark technique [ 15 ]. However, data of a RCT are with difficulty compareable to our data being a reflection of caudal blocks in children of different ages and routinely performed by anesthetists with various levels of training and not–as in RCT–by experts.…”
Section: Discussionmentioning
confidence: 99%
“…1 Despite its many benefits, ultrasound guidance is used in only about 3% of these blocks. 2 Occult spinal dysraphism incidence in healthy children is about 0.1% but can reach up to 2% in those with simple urogenital anomalies (especially hypospadias). 3 As compared to a normal spine (fig.…”
Section: Tethered Spinal Cord Syndrome Discovered During Ultrasound-g...mentioning
confidence: 99%